Upaya Penanggulangan HIV AIDS Di Yogyakarta - Sheila Soraya Choliq; Sepma Viraticha; Fatkhur Ruli Malik Qilsi (Pascasarjana Universitas Jember, 2022)
The progression of HIV epidemiology and advancements in HIV prevention and treatment technologies necessitate the availability of a range of prevention, treatment, and mitigation services to enhance the effectiveness of AIDS management. The Regional Strategies and Action Plan (SRAD) of Yogyakarta Municipality will be utilized as the policy direction and strategy in the effort to effectively-, efficiently-, measurably-, consistently-, and institutionally address HIV/AIDS issue. The aims: to understand the profile of the District Health Office of Special Region of Yogyakarta (SRY), and the efforts in controlling HIV/AIDS in Yogyakarta. The total area of the SRY is 3,133.15 km2. The SRY comprises 4 regencies and 1 city, including Kulon Progo Regency, Bantul Regency, Gunungkidul Regency, Sleman Regency, and Yogyakarta City, with a total population of 3,882,288 individuals. The cumulative number of HIV cases in Yogyakarta Municipality until June 2022 is 4,248 cases, and there have been 1,966 cases of AIDS. In addition, HIV cases continue to increase annually. To address this issue, it is necessary to involve Policy Stakeholders in the Yogyakarta Municipality Government, as well as Cross-Program and Cross-Sectoral collaboration according to their respective roles. With the increasing cases of HIV/AIDS, prevention and control efforts also need to be carried out in accordance with the policies for the prevention and control of HIV/AIDS in SRY as regulated by the legislation